2003
DOI: 10.1227/01.neu.0000068863.37133.9e
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vasospasm after Subarachnoid Hemorrhage: Putative Role of Inflammation

Abstract: Cerebral vasospasm is a common, formidable, and potentially devastating complication in patients who have sustained subarachnoid hemorrhage (SAH). Despite intensive research efforts, cerebral vasospasm remains incompletely understood from both the pathogenic and therapeutic perspectives. At present, no consistently efficacious and ubiquitously applied preventive and therapeutic measures are available in clinical practice. Recently, convincing data have implicated a role of inflammation in the development and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
289
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(301 citation statements)
references
References 126 publications
8
289
0
4
Order By: Relevance
“…Notably, a little cluster of inflammation genes, including PGES, CD14 and TIMP1 were upregulated in the early phase of SAH. These results coincide with results of SAH-related inflammatory reactions in numerous studies reported in the literature (14,15). TIMP1 expression was differentially regulated in a markedly similar pattern to that of MMP9 in acute activation following 2 h of 1-hemorrhage cerebrum SAH, suggesting that an imbalance of MMP9/TIMP1 regulation is implicated in the acute phase of SAH.…”
supporting
confidence: 90%
“…Notably, a little cluster of inflammation genes, including PGES, CD14 and TIMP1 were upregulated in the early phase of SAH. These results coincide with results of SAH-related inflammatory reactions in numerous studies reported in the literature (14,15). TIMP1 expression was differentially regulated in a markedly similar pattern to that of MMP9 in acute activation following 2 h of 1-hemorrhage cerebrum SAH, suggesting that an imbalance of MMP9/TIMP1 regulation is implicated in the acute phase of SAH.…”
supporting
confidence: 90%
“…1, 4,6,7 Inflammatory response with cytokine release is associated with severity of illness, clinical outcome and occurrence of CVS in patients with aSAH. [8][9][10] Higher levels of interleukin (IL)-6 in the cerebro-spinal fluid (CSF) have been linked to the occurrence of CVS and worse outcome. [10][11][12][13] Further, the occurrence of systemic inflammatory response syndrome has been linked to the development of CVS and worse outcome in patients with aSAH.…”
Section: Introductionmentioning
confidence: 99%
“…Large vessel and small vessel spasm may not result from the same mechanism nor do they likely have the same mechanism to cause functional deficit or morphologic brain injury. Among others, putative processes such as cortical spreading ischemia and activation of specific inflammatory pathways are currently topics for intense research [13,14]. Contributions from the laboratory will likely guide new therapeutic approaches in this field.…”
mentioning
confidence: 99%